Incidencia y afectación del secuestro extorsivo en la población de cantón Santo Domingo de los Colorados en el año 2023 - Salinas Jiménez, Segundo Bartolomé (2024)
The incidence and impact of extortive kidnapping in Santo Domingo canton during the 2023 has shown an alarming increase, reflecting a worrying perspective in the context of security in Ecuador. This crime, which has experienced an increase throughout our country, has become more accessible to criminals of diverse profiles, which has expanded its reach beyond high- income victims. Therefore, the general objective was to analyze the incidence and impact of extortive kidnapping in the population of Santo Domingo de los Colorados canton in the year 2023, proposing alternative prevention measures. For which the methodology used was a descriptive, documentary research, with a mixed approach through the use of inductive - deductive, historical and statistical methods, the measurement instruments applied to collect the information were a structured based survey with the application of the Likert scale and an interview guide, which were applied to the population under investigation, which was fifty citizens and five provincial judges. In this sense, the main results show that the population investigated expressed that the measures taken in the canton by the State through the state of emergency decrees have not generated the necessary impact, in the same way the judges described that the rates of extortive kidnapping have been increasingly frequently, due to the presence of criminal gangs that have been establishing themselves in the canton, however, the lack of speed in the processes has also generated stagnation, despite the fact that it works jointly with the Unidad Nacional de Investigación Antisecuestro y Extorsión (UNASE) of the National Police. Finally, it is proposed to develop strategies with a comprehensive plan to prevent extortive kidnapping which promotes citizen security.